Effect of pre and post-natal nutrition on the performances of ewes and lambs under semi intensive rearing system (Bangladesh Journal of Livestock Research, 2020)
The study was conducted to know the effect of different levels of pre and post-natal nutrition on the performances of ewes and their lambs until 1 year of age and the profitable slaughter age of lambs under semi intensive system. Twenty eight (28) native Bengal ewes at 7 weeks of gestation were randomly assigned to four groups (T0, T1, T2, T3) and supplemented with a concentrate mixture at 0.0, 1.0, 1.5, 2.0% of their body weight respectively. Ewes were allowed to graze 8 hours daily. Creep mixture (20 g/lamb/day) was provided to lambs from 2 weeks age with an increment of 10 g/lamb/week. After weaning, 20 growing male lambs were selected and reared 01 year of age with concentrate mixture at 1.5% of their body weight and 8 hours grazing irrespective of treatment groups. Parameters like, ewe’s litter size, daily milk yield, post-partum heat and lamb’s birth weight, weaning weight, live weight at 06, 09 and 12 months were recorded. The data were analyzed in an ANOVA with CRD by using SPSS v. 20. The mean differences were tested by DMRT at a probability level of P